A new family of iron(II)-cyclopentadienyl compounds shows strong activity against colorectal and triple negative breast cancer cells - Pilon, Adhan (2020)
The following is available online, Figure S1—1H NMR spectrum of complexes 6, in acetone-d6, Table S1. Bond lengths [Å] and angles [°] for [Fe(η5-Cp)(CO)(PhCN)(PPh3)][CF3SO3] 1, [Fe(η5-Cp)(CO)(p-NCPhNH2)(PPh3)][CF3SO3] 4 and [Fe(η5-Cp)(CO)(p-NCPhBr)(PPh3)][CF3SO3] 5, Table S2. Relevant TD-DFT (PBE0) excitation energies (λ), oscillator strengths (f) and compositions (only those > 5% are shown), for complexes 1–6, compared with experimental data (λexp). Both calculated and experimental values were obtained in dichloromethane, Figure S2—UV-Vis spectra of complexes 1–6 in DMSO along the 24 h study, Figure S3—UV-Vis spectra of complexes 1–6 in DMSO/DMEM mixture along the 24 h study and its variation plot (%) (bottom), Figure S4. ‘FeCp’ compounds affect the colony formation ability of SW480 cell line. Analysis of the colony formation ability, after 48 h of incubation with 1/4 IC50 and IC50, in SW480 cell line. Representative images of colony formation assay in SW480 cell line, Figure S5. ‘FeCp’ compounds induce apoptosis colorectal cancer-derived cell line. Apoptotic cell death was analyzed by Annexin V fluorescein isothiocyanate (AV-FITC) and propidium iodide (PI) assay in SW480 cells, after incubation with IC50 and 2×IC50 concentrations for 48 h. Representative histograms of SW480 cell line double stained with AV and PI, Table S4. Crystal data and structure refinement for [Fe(η5-Cp)(CO)(PhCN)(PPh3)][CF3SO3] 1, [Fe(η5-Cp)(CO)(p-NCPhNH2)(PPh3)][CF3SO3] 4 and [Fe(η5-Cp)(CO)(p-NCPhBr)(PPh3)][CF3SO3] 5.